2014
DOI: 10.1007/s10878-014-9795-0
|View full text |Cite
|
Sign up to set email alerts
|

$$k$$ k -Power domination in block graphs

Abstract: The power system monitoring problem asks for as few as possible measurement devices to be put in an electric power system. The problem has a graph theory model involving power dominating set in graphs. The concept of k-power domination, first introduced by Chang et al. (Discret Appl Math 160:1691-1698, 2012, is a common generalization of domination and power domination. In this paper, we present a linear-time algorithm for k-power domination in block graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Cyanoacetamides 327 , previously readily obtained by simply mixing methyl cyanoacetate with primary and secondary amines, could be used as the substrates in the Gewald reaction . Dömling et al.…”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
“…Cyanoacetamides 327 , previously readily obtained by simply mixing methyl cyanoacetate with primary and secondary amines, could be used as the substrates in the Gewald reaction . Dömling et al.…”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
“…Algorithms have been developed for solving the k ‐PDSP on specific graphs. For example, linear time algorithms have been introduced for finding optimal solutions in case of trees (Chang et al, 2012) and block graphs (Liao, 2016; Wang, Chen, & Lu, 2016). It is interesting to note that the minimal k ‐PDS for k > 1 are often of very small sizes; for instance, in Sundara Rajan, Anitha, and Rajasingh (2015) it has been shown that the 2‐PDS is of size 2 for torus, twisted torus, and certain bipartite graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [6] generalized the power domination to k-power domination by replacing the OR 2 with the following observation rule: If an observed vertex v has at most k unobserved neighbors, then v will send a message to all its unobserved neighbors. The definition also can be found in [21].…”
Section: Introductionmentioning
confidence: 99%
“…The k-power domination number of G, denoted by γ p,k (G), is the minimum cardinality of a k-power dominating set of G. When k = 1, The k-power domination is usual power domination. Both power domination and k-power domination are now well-studied in the literature (see, for example, [1,6,8,9,10,12,21,23,25]).…”
Section: Introductionmentioning
confidence: 99%